An Argument for the Test of Proportionality in Concreto: Silenced Voices from the Margins to the Center - Clérico, Laura; Aldao, Martín (Springer Science and Business Media B.V., 2021)
As a four-step exam, proportionality has become a well-known technique of rights adjudication. Moreover, we claim, among others, that as a framework for argumentation, and through modulation, it can be used in a manner that enables courts to compensate structural inequality patterns, allowing the voices and claims of people in situations of vulnerability. In order to corroborate our thesis, we contrast the application of proportionality by majority and minority votes in a case ruled by the ECtHR about the right of a woman to choose her residence. While both draw upon the exam, the first one opts for a general approach rendering invisible the intersectional layers of discrimination (poverty and gender) that undermines the applicant standing. On the contrary, the dissenting opinion opts for a thorough test (in concreto) able to account for the poverty and gender dimensions of the case. In doing so, we show the potentiality of the test of proportionality in concreto that allows questioning already established categories by empowering marginalized voices, and lays a clear path on how to deal with that process.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Argumentative empowerment; Concrete approach; Gender and poverty; General approach; Proportionality